1913-2013 100 anni di studi agrari e forestali nella Villa Granducale delle Cascine a Firenze - SURICO, GIUSEPPE (Firenze University Press, 2013)
One hundred have passed, and the journey continues. This work was created by a group of professors of the (former) Faculty of Agriculture of the University of Florence, and has the sole purpose of telling, through a few significant subjects, about the first one hundred years (1913-2013) of an institution which, thanks to its researchers, technicians and administrative department, has contributed as one to the advancement of knowledge in the Agricultural Sciences and, in the local area, to the success of the agri-food sector in Tuscany. However, the real protagonists of this work are not only the Teachers of the School of Agricultural and Forestry Sciences of the University of Florence, but also the thousands of students who, over a century, have attended the National Forestry Institute first, and then the Faculty, and who have brought the fruits of the teachings they received in Florence to Italy and to the whole world.